SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN BEASISWA DOKTOR UNTUK DOSEN POTENSIAL DENGAN METODE SMART - Ardi Ardi; Irfan Fadhli (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2020)
Abstract: The role of lecturers in higher education is one of the most influential parts of the quality of students produced. Lecturer educational qualifications are also an important aspect of improving academic and institutional quality. Selection of foundation scholarships in the form of doctoral education currently has problems in choosing prospective lecturers. In the selection of doctoral scholarships for potential lecturers, there is still subjectivity in their selection manually. As a supporting medium in determining the selection of potential lecturers to obtain doctoral education foundation scholarships and testing the SMART (Simple Multi Attribute Rating Technique) method to provide scholarship recommendations for prospective lecturers. The selection process uses the SMART method because this method is able to solve multi-criteria problems from the foundation, in this case the Chancellor of the Indonesian Community Development University. Furthermore, the criteria are processed using an application built using the PHP and MySQL programming languages to test these criteria. From the application built, it can be concluded that Yuanita, M.Si with a score of 0.7342 and Khairuddin Tampubolon, M.Si with a score of 0.6311 are entitled to get a doctoral education scholarship from the foundation. Then subjective and computerized decisions can be obtained in this study..            Keywords: Decision Support Systems; Mysql; PHP ; Potential Lecturer Scholarships, Simple Multi Attribute Rating Technique.  Abstrak: Peran dosen di perguruan tinggi adalah salah satu bagian paling berpengaruh dari kualitas mahasiswa yang dihasilkan. Kualifikasi pendidikan dosen juga merupakan aspek penting untuk meningkatkan kualitas akademik dan kelembagaan. Pemilihan beasiswa yayasan dalam bentuk pendidikan doktor saat ini memiliki masalah dalam memilih calon dosen. Dalam pemilihan beasiswa pendidikan doktoral untuk dosen potensial masih ada subjektivitas serta dalam seleksi mereka secara manual. Sebagai media pendukung dalam menentukan seleksi dosen potensial untuk memperoleh beasiswa yayasan pendidikan doktoral dan menguji metode SMART (Simple Multi Attribute Rating Technique) untuk memberikan rekomendasi beasiswa bagi calon dosen. Untuk proses seleksi menggunakan metode SMART karena metode ini mampu menyelesaikan masalah multi-kriteria dari yayasan dalam hal ini Rektor Universitas Pembinaan Masyarakat Indonesia. Selanjutnya, kriteria diproses menggunakan aplikasi yang dibangun menggunakan bahasa pemrograman php dan mysql untuk menguji kriteria ini. Dari aplikasi yang dibangun dapat ditarik kesimpulan bahwa Yuanita, M.Si dengan nilai 0,7342 dan Khairuddin Tampubolon, M.Si  dengan nilai 0,6311 berhak mendapatkan beasiswa pendidikan doctoral dari yayasan. Kemudian keputusan subyektif dan terkomputerisasi dapat diperoleh dalam penelitian ini. Kata kunci: Beasiswa Dosen Potensial; Mysql; PHP; Simple Multi Attribute Rating Technique; Sistem Pendukung Keputusan.